Legal Protection Against Registered Marks Due to Actions Trademarks Squatting Based on Good Faith in Indonesia - Aristiani, Putu Tissya Poppy; Bagiastra, I Nyoman (Kertha Patrika, 2023)
The purpose of this writing is to examine, analyze, and elaborate on the concept of trademark squatting actions and legal protection for registered trademarks due to trademark squatting actions based on good faith in Indonesia. This study is written using normative research methods using statutory approaches, conceptual approaches, and analytical approaches. This study's results shows that the concept of Trademarks Squatting is not regulated in the provisions of the Law on Trademarks and Geographical Indications, but at the international level, WIPO explains that trademark squatting is the act of registering or using a mark which is generally a well-known foreign brand, where the mark has not been registered in a country or the mark has been registered but has never been used by the owner of the mark concerned. As well as, the legal protection of registered trademarks due to trademark squatting in Indonesia, in particular, the possibility of taking legal action against other parties who illegally use a Mark that is essentially similar in terms of rules or its wholeness for similar products or services in the form of a claim for compensations; and/or Termination of all actions related to the use of said Mark based on the stipulations of Article 83 point (1) of the Law on Trademarks and Geographical Indications.